A novel adoptive synthetic TCR and antigen receptor (STAR) T‐Cell therapy for B‐Cell acute lymphoblastic leukemia. Issue 8 (12th May 2022) - Wang, Jiasheng; Zhang, Xian; Zhou, Zhixiao; Liu, Yue; Yu, Li; Jia, Lemei; Yang, Junfang; Li, Jingjing; Yu, Hanyang; Li, Wenzhong; Liu, Guangna; Rui, Wei; et al.
Abstract: We developed a T‐cell‐receptor (TCR) complex‐based chimeric antigen receptor (CAR) named S ynthetic T CR and A ntigen R eceptor (STAR). Here, we report pre‐clinical and phase I clinical trial data (NCT03953599) of this T‐cell therapy for refractory and relapsed (R/R) B‐cell acute lymphoblastic leukemia (B‐ALL) patients. STAR consists of two protein modules each containing an antibody light or heavy chain variable region and TCR α or β chain constant region fused to the co‐stimulatory domain of OX40. T‐cells were transduced with a STAR‐OX40 lentiviral vector. A leukemia xenograft mouse model was used to assess the STAR/STAR‐OX40 T cell antitumor activity. Eighteen patients with R/R B‐ALL were enrolled into the clinical trial. In a xenograft mouse model, STAR‐T‐cells exhibited superior tumor‐specific cytotoxicity compared with conventional CAR‐T cells. Incorporating OX40 into STAR further improved the proliferation and persistence of tumor‐targeting T‐cells. In our clinical trial, 100% of patients achieved complete remission 4 weeks post‐STAR‐OX40 T‐cell infusion and 16/18 (88.9%) patients pursued consolidative allogeneic hematopoietic stem cell transplantation (allo‐HSCT). Twelve of 16 patients (75%) remained leukemia‐free after a median follow‐up of 545 (433–665) days. The two patients without consolidative allo‐HSCT relapsed on Day 58 and Day 186. Mild cytokine release syndrome occurred in 10/18 (55.6%) patients, and 2 patients experienced grade III neurotoxicity. Our preclinical studies demonstrate super anti‐tumor potency of STAR‐OX40 T‐cells compared with conventional CAR‐T cells. The first‐in‐human clinical trial shows that STAR‐OX40 T‐cells are tolerable and an effective therapeutic platform for treating R/R B‐ALL.